Application of nanomagnetic bead-based DEHP detection and Doppler ultrasound in diagnosis of prenatal foetal malformations. (30th September 2020) - Ge, Ming-Zhu; Hou, Cai-Xia; Huang, Xiu-Ying; Wang, Yu
Foetal malformations mainly refer to abnormal foetal structure and chromosomes in the womb. In recent years, with the popularisation and application of electronic products and the rise of the elderly maternal population, it has caused some impact on the quality of pregnant women's eugenics. However, foetal heart disease is not exactly the same as paediatric heart disease. The foetus is connected to the placenta through the umbilical cord. It has its own independent circulatory system and is inseparable from the mother. Although ultrasound technology has been introduced to the foetal heart examination for more than 40 years, and its equipment and diagnosis technology has made great progress and development in recent years, owing to the influence of various factors from the mother and foetus, the fine recognition of the foetal heart structure and the determination of various common or complex diseases need further improvement. In this paper, 1526 pregnant women who received antenatal ultrasound examination from January 2018 to May 2019 were selected as the research subjects. All were examined with colour Doppler ultrasound, and the results were analysed using autopsy and postnatal ultrasound examination results as criteria. The value of pre-colour ultrasonography, the results showed that 35 cases of foetal congenital malformations were detected by prenatal colour Doppler ultrasound, no misdiagnosis, five cases of complex congenital heart disease, 30 cases of common congenital heart disease, and common congenital heart disease Aortic translocation accounted for the highest proportion of sexual heart disease. The use of colour Doppler ultrasound for the diagnosis of foetal heart malformations can effectively detect the type of foetal heart malformations, which can provide a reliable basis for physicians to fully understand the foetal heart condition of pregnant women and follow-up symptomatic treatment, and improve the quality of newborn births.